Comparative functional analyses of the movement and coat proteins of grapevine Pinot gris virus, encoded by symptomatic and asymptomatic variants - Jaksa-Czotter, Nikoletta; Demián, Emese; Sáray, Réka; Salánki, Katalin; Várallyay, Éva (Frontiers in Plant Science, 2025)
Using small RNA high-throughput sequencing (HTS), we previously demonstrated the widespread distribution of grapevine Pinot gris virus (GPGV) in Hungarian vineyards. This trichovirus has been associated with a disease known as grapevine leaf mottling and deformation (GLMD). However, since GPGV has been detected in both symptomatic and asymptomatic plants, its exact role in GLMD disease is not well-characterised. Studies addressing this question suggested that differences in the GPGV susceptibility of the grapevine cultivars and the presence of variants of the virus could affect symptom development. Being able to suppress various steps of the RNA interference-based defence reactions, the viral suppressor of RNAi (VSR), encoded by the ORF3 of GPGV, can also alter the symptom development. In the present study, we compared the VSR activity of the ORF3-encoded coat protein of symptomatic and asymptomatic GPGV variants and found that both possess VSR activity. Testing the VSR activity of the ORF2-encoded movement proteins from the two variants, using a GFP-based transient gene expression assay, we found that the GPGV-MP has weak systemic VSR activity. Moreover, we found that the transient expression of the MP variants induced necrosis in the infiltrated leaves, which was stronger in the case of the symptomatic variant. To functionally characterise the crucial sequence elements of MP responsible for this difference in the necrosis between symptomatic and asymptomatic variants, the necrosis-inducing activity of GPGV-MP encoded by different natural and recombinant variants was tested. Differences in the GPGV-MP necrosis-inducing activity suggested that, besides the previously described C/T polymorphism, different phosphorylation patterns of the GPGV-MP may contribute to symptom development.